Topological Indices of Novel Drugs Used in Cardiovascular Disease Treatment and Its QSPR Modeling - Fozia Bashir Farooq; Nadeem Ul Hassan Awan; Saima Parveen; Nazeran Idrees; Salma Kanwal; Tarig A. Abdelhaleem (Journal of Chemistry)
A topological index is a score function that changes each molecular structure to a unique real number. It aids in determining the physicochemical and biological properties of a wide range of drugs, and it more accurately reflects the theoretical properties of drugs. The task is accomplished through the use of degree-based topological indices (TIs). Heart disease refers to a group of disorders that affect our hearts. Heart diseases include blood vessel disorders such as irregular heartbeat and heart muscle disease. In this article, Eliquis, metoprolol, valsartan, etc., and other drugs employed to treat cardiovascular disease are studied and the QSPR analysis goal will probe the mathematical relationship of properties such as (polarity, boiling point, enthalpy, etc.) and assorted descriptors associated to drug’s structure. The present study on TIs imposed on drugs was found to have a good correlation with physical properties.